Organized Scientific Diaspora and Its Contributions to Science Diplomacy in Emerging Economies: The Case of Latin America and the Caribbean - Echeverría-King, Luisa F.; Camacho Toro, Reina; Figueroa, Pedro; Galvis, Laura A.; González, Alejandra; Suárez, Verónica Rossana; Torres Atencio, Ivonne; Widmaier Müller, Claudia Natalie (Frontiers in Research Metrics and Analytics, 2022)
The current knowledge society has driven an unprecedented mobility of people, especially scientists, from emerging economies to developed countries. This mobility can allow the development of human talent and the access to first class infrastructure and resources, but it can also mean a loss for emerging economies due to the phenomenon of brain drain. To counteract this situation, some countries in Latin America and the Caribbean have developed models for the articulation of their scientific diaspora in projects and programs, with the aim of exchanging knowledge and capitalizing on human and technical resources to advance science, technology and innovation systems. Likewise, science diplomacy has become a tool for interlinking the work of various actors in order to advance the solution of national, transnational or global problems through scientific advice. Scientific diasporas are vital in new structures of cooperation, enabling them to innovate and solve problems jointly, advising their countries of origin and articulating policies and programs. This research seeks to analyze the interactions and initiatives identified between the organized scientific diaspora from Latin America and the Caribbean and their countries of origin in relation to science diplomacy processes, providing recommendations and proposals for public policy to improve the interaction between the diaspora and the governments of their countries of origin. Results show that diaspora organizations from Latin America and the Caribbean engage with governmental and non-state actors and are active science diplomacy stakeholders promoting the scientific developments of their country or their researchers, as well as enabling access to research resources creating alliances for scientific, institutional and academic collaborations. In the cases studied, these efforts are planned and executed by the diaspora without responding to any science diplomacy strategy of the country. Policies and programs are needed to effectively link the scientific diaspora organizations to the interests of the countries.